Determinants of Audit Delay: Evidence From the Indonesia Stock Exchange - Adelia, Fina; Luthan, Elvira (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The current era, characterized by rapid changes in business dynamics and financial regulations, demands a deep understanding of audit delay. This study aims to empirically test and analyze the effect of audit fees, profitability, audit tenure, audit opinions, and audit committee expertise on audit delay. The sample used was 96 observations consisting of property and real estate sector companies listed on the Indonesia Stock Exchange during 2019 to 2022. Then the data was analyzed using the classical assumption method and multiple linear regression. The results of this study indicate that audit fees and audit tenure do not have a significant effect on audit delay, while profitability, audit opinions, and audit committee expertise have a negative effect on audit delay. This study expands the literature by adding testing on variables that have not been widely studied in the causes of audit delay. The implications of this study are expected to provide more recent insights to companies and professionals regarding several factors that can cause audit delays.